1999
DOI: 10.1562/0031-8655(1999)070<0751:kaotli>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of the Light-induced Fluorescence Quenching in Light-harvesting Chlorophyll a/b Pigment–Protein Complex of Photosystem II

Abstract: We carried out a kinetic analysis of the light-induced fluorescence quenching (AF) of the light-harvesting chlorophyll a/b pigment-protein complex of photosystem 1 1 (LHCII) that was first observed by Jennings et aL (Photosynth. Res. 27, 5764, 1991). We show that during a 2 min light, 2 min dark cycle, both the light and dark phases exhibit blexponential kinetics; this is tentatively explained SAbbreviurions: Chl, chlorophyll; CMC, critical micellar concentration; DM, n-dodecyl p-D-maltoside; AF, light-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…Prolonged illumination of LHCII is associated with light-driven, reversible fluorescence quenching (Jennings et al, 1991;Gruszecki et al, 1994Gruszecki et al, , 1999Barzda et al, 1999). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Prolonged illumination of LHCII is associated with light-driven, reversible fluorescence quenching (Jennings et al, 1991;Gruszecki et al, 1994Gruszecki et al, , 1999Barzda et al, 1999). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, as later investigations have shown, these reorganizations in thylakoid membranes and similar light-induced reversible changes in isolated lamellar aggregates of LHCII originated from a novel, biological thermo-optic effect (Barzda et al 1996;Cseh et al 2000;Dobrikova et al 2003). It is also interesting to note that structural changes in LHCII have been shown to be accompanied by changes in the fluorescence yield (Barzda et al 1996(Barzda et al , 1999Grudzinski et al 2002). Hence, it can be concluded that albeit these changes might be associated with qE, the two phenomena are not strictly correlated with each other.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that isolated LHCII complexes exhibit light-induced reversible fluorescence quenching, which resembles to a certain extent the NPQ in chloroplasts (Jennings et al 1991), and which is associated with structural reorganizations (Barzda et al 1999;Grudzinski et al 2002). It has also been shown that loosely stacked lamellar aggregates of LHCII, which retain substantial amounts of lipids, possess the ability of undergoing gross light-induced reversible structural reorganizations dramatically affecting the long-range chiral order of their chromophores (Barzda et al 1996).…”
Section: Introductionmentioning
confidence: 99%